INTEGRASI KONSELING KELOMPOK DAN INDIVIDU BERBASIS ISLAM UNTUK REDUKSI PROKRASTINASI AKADEMIK SISWA - Putri Rahmadani; Dina Hajja Ristianti; Beni Azwar; Sumarto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Academic procrastination is a behavior of delaying the completion of academic tasks that frequently occurs among students and has an impact on decreasing academic achievement, discipline, and self-control. This study aims to analyze the integration of Islamic-based group and individual counseling in reducing students’ academic procrastination. The study employed a qualitative method using a library research approach through the analysis of various relevant journals, books, and scientific articles published between 2020 and 2025. Data were collected through documentation techniques, while data analysis used content analysis. The findings indicate that academic procrastination is influenced by low learning motivation, weak self-control, low self-efficacy, and the influence of social media. Islamic-based group counseling is effective in improving students’ motivation, social support, and discipline through group dynamics, while Islamic-based individual counseling helps students understand personal problems and improve self-control through spiritual approaches such as self-reflection (muhasabah) and self-management. The integration of these two services demonstrates that strengthening Islamic spiritual values such as discipline, responsibility, and appreciation of time can help students reduce procrastination behavior. Therefore, Islamic-based counseling services can serve as a more holistic approach in overcoming students’ academic procrastination